ANALISIS PEMASARAN DODOL RUMPUT LAUT PADA UMKM CITARASAKU DI KECAMATAN MARAWOLA KABUPATEN SIGI - Sasmita, Sasmita; Kassa, Saharia; Muis, Abdul (AGROTEKBIS, 2018)
The purpose of this study is (1) analyze the form of marketing chain dodol seaweed on UNKM Citarasaku in District Marawola Sigi, (2) analyzing the marketing margin of dodol seaweed on UNKM Citarasaku, (3) analyze the part of the price received by producers dodol seaweed on UNKM Citarasaku, (4) analyze the efficiency of marketing dodol seaweed on UNKM Citarasaku. This study conductd at Jl. Kramat Jaya No. 51 District of Marawola Sigi in November to December 2015. The data used in this study using two types of data, primary data and secondary data. Analysis of the data used is the marketing margin analysis, the analysis part of prices received by producers and marketing efficiency analysis. Results of the analysis showed that there are two chain of marketing dodol seaweed on UNKM Citarasaku namely (1) Manufacturer  Retailers consumen (2) Manufacturers  Consumer. Marketing margin on the first chain from manufacturers to retailers Rp. 5,000 for the packaging of 150 g and Rp. 5,000 for packing 300 gr. While the second chain can not be found because no marketing margin marketing agencies involved in the marketing process. So on the first chain is the total margin of Rp. 10,000. Part of the price received by the producer seaweeds dodol UNKM Citarasaku the first chain that is 61.5% for the packaging of 150 g and 75% for the packaging of 300 g for the second part of prices received by producers seaweeds dodol both have the same value, namely 1% for both the packaging. The efficiency of the marketing chain dodol seaweed on UNKM Citarasaku on the first chain of 1.38% and a second marketing channel of 1.29%. The first marketing chain and second marketing chain is second one themost efficient marketing chain where the value is 1.29%. Keywords: Dodol Seaweed, Marketing, Producer.